Qualitative detection of Naringin from Bridelia montana var. montana (Roxb.) Willd - Dhimdhime1 and A. L. Vaidya3, V. T. Narwade1, A. A. Waghmare2, S. D. (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Flavanones from Bridelia montana var. montana (Roxb.) Willd. were extracted by using different solvents. It was identified and detected by Paper Chromatography (PC) and spectroscopic method. Flavanone like naringin was qualitatively detected from B. montana var. montana (Roxb.) Willd.